Bourdieu and the sociology of music education - Burnard, Pamela; Hofvander Trulsson, Ylva; Söderman, Johan (Farnham Ashgate, 2015)
Pierre Bourdieu has been an extraordinarily influential figure in the sociology of music. For over four decades, his concepts have helped to generate both empirical and theoretical interventions in the field of musical study. His impact on the sociology of music taste, in particular, has been profound, his ideas directly informing our understandings of how musical preferences reflect and reproduce inequalities between social classes, ethnic groups, and men and women. Bourdieu and the Sociology of Music Education draws together a group of international researchers, academics and artist-practitioners who offer a critical introduction and exploration of Pierre Bourdieus rich generative conceptual tools for advancing sociological views of music education. By employing perspectives from Bourdieus work on distinction and judgement and his conceptualisation of fields, habitus and capitals in relation to music education, contributing authors explore the ways in which Bourdieus work can be applied to music education as a means of linking school (institutional habitus) and learning, and curriculum and family (class habitus). The volume includes research perspectives and studies of how Bourdieus tools have been applied in industry and educational contexts, including the primary, secondary and higher music education sectors. The volume begins with an introduction to Bourdieus contribution to theory and methodology and then goes on to deal in detail with illustrative substantive studies. The concluding chapter is an extended essay that reflects on, and critiques, the application of Bourdieus work and examines the ways in which the studies contained in the volume advance understanding. The book contributes new perspectives to our understanding of Bourdieus tools across diverse settings and practices of music education.Contents: Foreword, Diane Reay; Contextualising Bourdieu in the field of music and music education, Johan Söderman, Pamela Burnard and Ylva Hofvander Trulsson; Hip-hop Academicus: examples of Bourdieusian field effects within two hip-hop spaces, Johan Söderman; Striving for class remobility: using Bourdieu to investigate music as a commodity of exchange within minority groups, Ylva Hofvander Trulsson; Singing gender and class: understanding choirboys musical habitus, Clare Hall; Masculine domination in private-sector popular music performance education in England, Gareth Dylan Smith; Now were the musicians: using Bourdieus concepts of habitus, capital and field to analyse informal learning in Canadian music education, Ruth Wright; Bourdieu applied in the analysis of conservatoire learning cultures, Rosie Perkins; Producing a classical habitus: reconsidering instrumental music teaching methods, Dan Sagiv and Clare Hall; DJ and MC habitus and Skillz in peer-led learning cultures, Garth Stahl and Pete Dale; Pierre Bourdieu and the autonomy of art: the idea of art as critique, Øivind Varkøy; Analysing educational choices by class-diversifying, feminising and moralising Bourdieus theoretical framework, Berglind Rós Magnúsdóttir; The geography of music education: establishing fields of action, Patrick Schmidt; Working with Bourdieus cultural analysis and legacy: alignments and allegiances in developing career creativities, Pamela Burnard; Bourdieu and musical learning in a globalised world, Ylva Hofvander Trulsson, Pamela Burnard and Johan Söderman; Coda: reflecting on the use of Bourdieus tools from outside the fields of music and music education, Rene Wiedner; Glossary; Index.About the Editor: Pamela Burnard is Professor of Arts, Creativities and Education, University of Cambridge, UK. Her research interests include diverse creativities, digital technologies, intercultural arts, music education and industry. Her books include Musical Creativities in Practice, Creativities in Higher Music Education, Music Education with Digital Technologies and Teaching Music Creatively. She is Co-convenor of the British Educational Research Association (BERA) Creativity in Education SIG and Convenor of the Creativities in Intercultural Arts Network.Ylva Hofvander Trulsson is Senior Lecturer at the Faculty of Fine and Performing Arts at Lund University, Sweden. She was visiting scholar / postdoc at the Faculty of Education, University of Cambridge, UK (2012-2014). Her research focuses on perspectives on class formation in relation to parents choices, concerted cultivation, migration and social mobility. Ylva is also visiting scholar at Hedmark University College, Norway, (2013-2016) in association with the research project Musical gentrification and socio-cultural diversitiesýý. Ylva has been recognized nationally and internationally for her theory-driven research of music education, minorities and social mobility.Johan Söderman is Associate Professor in Music Education at Malmö University and Reader in Music Education at Lund University, Sweden. He has conducted research concerned with hip-hop cultural studies, and education. Between 2009 and 2011, he was a visiting scholar at the Department of Music and Music Education at Teachers College, Columbia University, USA. His research interests are the Scandinavian educational tradition called folkbildning, academisation processes of youth music and social mobilisation/marginalisation in post-industrial society.Pamela Burnard has a profile page on the University of Cambridge website